“Silent” dysphasia of the knee joint - Roy, Iryna; Bayandina, Оlena; Belaya, Iryna; Zinchenko, Vitaliy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article contains results of a 2-staged examination of 500 newborns with the purpose to reveal disturbances in their hip joint formation, as well as to assess the informativeness of the orthopaedic visual examination and ultrasonographic examination. At the 1st stage, history taking and clinical examination with necessary clinical tests were made. At the 2nd stage, ultrasonographic examination according to the Graf’s method was performed. The orthopaedic examination sensitivity was 75 %, its specificity was 66 %, and the validity was 69 %; a failure in the coincidence of diagnoses was observed in 31 % of patients. It is important to notice that the ultrasonographic examination revealed a group of children, whose hip joint pathology was not diagnosed during the clinical examination. It is these cases of hypodiagnosis (25 %) that we suggest to call “silent” dysplasia.